Deadliest creatures - Allen, Peter; Cropp, Ben ([S.l.] : Start Entertainments, 1994)
The video shows sharks, snakes, spiders & scorpions splash, sting and scurry across sand, sea and surfs.
Narrated by Peter Allen
Title from data sheet
Keywords: Dangerous aquatic animals; Dangerous reptiles; Insects